Automated visual inspection of IC packages - U Maung Maung Thet (2008)
This dissertation focuses on some issues on the automatic inspection of IC packages and presents computer vision based techniques that were developed to perform automatic IC print mark inspection, automatic IC leads inspections, and inspection of the batch numbers on IC packages using the OCR system.